PENGEMBANGAN BAHAN AJAR TEMATIK TEMA 6 CITA-CITAKU DENGAN PENDEKATAN KONTEKSTUAL DI KELAS IV SD - Siti Khovifah Kesuma; Sujarwo Sujarwo (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to design an existing material into a new material format with the aim of creating teaching and learning activities that are more active, interesting and meaningful than before, and do not conflict with the curriculum. This development research uses a contextual approach. The type of research used is Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. However, in this study, researchers only carried out the ADDIE development model only up to the Development stage. This research was conducted at SDS Al-Washliyah 80 Kisaran. The object of research is the reviewer of material experts, teaching materials experts and learning experts or fourth grade elementary school teachers. The results of the study include validation 1 with material experts obtaining a score of 71.2 with appropriate criteria. Furthermore, in validation 2 by material experts, it obtained a score of 81.6 with very feasible criteria. The results of validation with teaching materials experts at stage 1 obtained a score of 69,6 with appropriate criteria and at stage 2 validation with teaching materials experts obtained a score of 85.6 in the very feasible category. The results of the validation by learning experts or teachers obtained a score of 92.6 with very decent criteria. From the scores obtained from the three experts, it can be said that the thematic teaching materials for theme 6 my ideals with a developed contextual approach can be used in the learning process